One-step chromatographic method to purify -lactalbumin from whey for nanotube synthesis purposes - Fuciños, C. (2019)
A one-step anion-exchange chromatography method (NaCl gradient elution on a DEAE Sepharose Fast Flow gel column) was developed to purify -lactalbumin (-LA) from whey protein isolate. -LA nearly 100% pure (based on the total protein content) was obtained with a yield of about 39%. Besides pure -LA, which was the main objective of this work, highly pure -lactoglobulin was also obtained with a yield of about 59%. The high purity of the obtained -LA samples allowed its use to synthesise protein nanotubes with excellent gelation properties for their use as food thickeners and bioactive carriers. The samples purity degree obtained (based on the total protein content) was critical in the formation of proper nanotubes instead of random aggregates, which produced opaque and weak gels, less useful for food applications.